China as number one? : the emerging values of a rising power - Zhong, Yang, 1960-; Inglehart, Ronald; Michigan Publishing (University of Michigan) (Ann Arbor, Michigan : University of Michigan Press, 2024)
One of the most significant global events in the last forty years has been the rise of China- economically, technologically, politically, and militarily. The question on people's minds for decades has been whether China will replace the United States as a superpower in the near future. But for China, this power must be comprehensive - having strong economic and militant forces are only two pieces of the puzzle. China must also possess soft power, such as attractive ideologies, values, and culture. China as Number One? explores China's soft powers through the eyes of Chinese citizens. Utilizing data from the World Values Survey, the contributors to this collection explore the potential soft power of a rising China by examining its residents' social values. A comprehensive study of changes and continuities in the political and social values of Chinese citizens, the book examines findings in the context of evolutionary modernization theory and cross-national comparison.
Preface / Mary E. Gallagher and Yang Zhong -- Introduction / Ronald Inglehart and Yang Zhong -- Democratic Authoritarianism: A Study of Chinese Political Orientations / Wenfang Tang -- Political Participation in China / Lingnan He and Dali L. Yang -- Postmaterialism in China / Yu Yan -- Contained Emancipative Values: Waves of Conservative and Liberal Trends in China / John James -- The Rise and Fall of Trust in Transitional China / Alfred M. Wu, Eduardo Araral, and Biao Huang -- Attitudes toward Religion, Science and Technology in China / Yang Zhong -- Conclusions / Yang Zhong and Ronald Inglehart.
Includes bibliographical references and index.
Sponsored by The Lieberthal-Rogel Center for Chinese Studies (LRCCS)
Keywords: Power (Social sciences) -- China -- 21st century; Public opinion -- China -- 21st century; POLITICAL SCIENCE / World / Asian; China -- Politics and government -- 2002-; China -- Social conditions -- 2000-; Print books